PENGARUH BEBAN KERJA DAN TUNJANGAN PROFESI TERHADAP KEPUASAN KERJA GURU MADRASAH TSANAWIYAH DI KABUPATEN TANAH LAUT - Alfianoor, Alfianoor; Abdurrahman, Akhmad (PPPM STIA Amuntai, 2019)
ALFIANOOR (2019) This study aims to (1) analyze the effect of workload on job satisfaction. (2) analyze the effect of professional allowances on job satisfaction. (3) analyze the effect of workload and professional allowances simultaneously on job satisfaction for Madrasah Tsanawiyah teachers in Tanah Laut Regency. The design of this study is based on a survey approach whose nature of this research is explanatory is a study that intends to explain the position of the variables studied and the relationship between one variable and another. The existing research variables are to predict the closeness of the influence of one to the other variables according to the criteria concerning the influence of workload and professional allowances on job satisfaction of teachers in the Madrasah Tsanawiyah Regency in Tanah Laut in a strong and in-depth manner using multiple regression analysis. The population were all 98 Madrasah Tsanawiyah teachers in Tanah Laut Regency. The sampling technique is Porpusive Sampling which is determined in advance and has a relationship with the study, which is as many as 42 ASN people at the Madrasah Tsanawiyah Negeri in Tanah Laut Regency who have received certification allowances. Data was collected through questionnaires and documentation. The analytical tool used in this study is descriptive statistical analysis and inferential statistical analysis with SPSS 20.0 for Windows. The results of the study show that (1) The effect of workload on job satisfaction of Madrasah Tsanawiyah teachers in Tanah Laut Regency based on the results of the t test is known that t count> t Table can be declared significant and proven. (2) That the results show the existence of professional allowances have a significant effect on teacher job satisfaction. (3) Workload and professional allowances have a significant effect simultaneously (together) on job satisfaction of Madrasah Tsanawiyah Teachers in Tanah Laut Regency based on the results of the F test known that F count> F Table. The better the workload given to Madrasah Tsanawiyah teachers in Tanah Laut District, the higher the level of job satisfaction. Keywords: Workload, Professional Allowance, Teacher Job Satisfaction